Christianity in modern China : the making of the first native Protestant church - Cheung, David, Ph. D. (Studies in Christian Mission, 2004)
Using mainly hitherto unstudied primary materials, this monograph studies a very significant episode in Chinese Christianity. Focusing on the origins and earliest history of Protestantism in South Fujian, this analytical-critical study investigates the evolution of the churches which pioneered in indigenisation and ecclesiastical union in China during the nineteenth century. Some subjects studied are primitive missionary objectives and methods, the relationship between the 'Talmage ideal' and the Three-self concept, and the nature and dynamics of 'native' religious work. Extremely useful is the critical assessment of South Fujian in terms of self-propagation, self-government, self-support and organic union. The key areas suggested for future research are also quite thought-provoking. The volume is especially valuable to social and church historians, missiologists and sociologists.